2014
DOI: 10.1371/journal.pone.0108196
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus and Risk of Age-Related Macular Degeneration: A Systematic Review and Meta-Analysis

Abstract: Age-related macular degeneration (AMD) is a major cause of severe vision loss in elderly people. Diabetes mellitus is a common endocrine disorder with serious consequences, and diabetic retinopathy (DR) is the main ophthalmic complication. DR and AMD are different diseases and we seek to explore the relationship between diabetes and AMD. MEDLINE, EMBASE, and the Cochrane Library were searched for potentially eligible studies. Studies based on longitudinal cohort, cross-sectional, and case-control associations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 74 publications
3
70
1
2
Order By: Relevance
“…Risk factors for AMD include diabetes, prior eye diseases and cardiovascular comorbidities. A meta‐analysis of nine cross‐sectional studies showed that diabetes was a risk factor for AMD (OR 1.21; 95% CI 1.00–1.45), especially for late neovascular AMD (OR 1.48; 95% CI 1.44–1.51), but not for geographic atrophy . By contrast, the Blue Mountains Eye Study showed that diabetes was a predictor of incident geographic atrophy but not neovascular AMD .…”
Section: Age‐related Macular Degenerationmentioning
confidence: 99%
“…Risk factors for AMD include diabetes, prior eye diseases and cardiovascular comorbidities. A meta‐analysis of nine cross‐sectional studies showed that diabetes was a risk factor for AMD (OR 1.21; 95% CI 1.00–1.45), especially for late neovascular AMD (OR 1.48; 95% CI 1.44–1.51), but not for geographic atrophy . By contrast, the Blue Mountains Eye Study showed that diabetes was a predictor of incident geographic atrophy but not neovascular AMD .…”
Section: Age‐related Macular Degenerationmentioning
confidence: 99%
“…Besides these differences in ethnical association, association with diabetes is frequently being reported for (late) AMD, too [7]. …”
Section: Introductionmentioning
confidence: 99%
“…18,19 Both diabetes and hypertension have been reported to be strong risk factors for NVAMD. 2023 Although the presence of HE might indicate a severe form of diabetic and hypertensive retinopathy, the proportion of patients with diabetes or hypertension in the group with HE was similar to the proportion without HE. However, the CATT study eligibility criteria excluded patients who had any concurrent intraocular condition such as diabetic retinopathy that might require medical or surgical intervention during the two years of the study or, that could likely contribute to loss of vision over the two year follow-up period.…”
Section: Discussionmentioning
confidence: 92%